Analytical modeling of effective conduction path effect (ECPE) on the subthreshold swing of DG-MOSFETs - Tiwari P.K.; Panda C.R.; Agarwal A.; Sharma P.; Jit S. (My University, 2025)
A closed form expression for the effective conduction path parameter of subthreshold conduction is presented for dual gate metal oxide semiconductor field effect transistor (DG MOSFET). Based on the effective conduction path an analytical expression of subthreshold swing is obtained. © 2009 IEEE.